2014
DOI: 10.1080/03043797.2014.903228
|View full text |Cite
|
Sign up to set email alerts
|

Professional development for design-based learning in engineering education: a case study

Abstract: Design-based learning (DBL) is an educational approach in which students gather and apply theoretical knowledge to solve design problems. In this study, we examined how critical DBL dimensions (project characteristics, design elements, the teacher's role, assessment, and social context) are applied by teachers in the redesign of DBL projects. We conducted an intervention for the professional development of the DBL teachers in the Mechanical Engineering and the Electrical Engineering departments. We used the Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Swan et al [26] explored a collaborative, design-based approach to improving the learning effects in core courses of an online program. Gómez Puente et al [27] boosted teachers to use the DBL theoretical framework to create teaching activities and proposed an immersive learning model to enhance teachers' professionalism. Baran and Uygun [28] outlined eight DBL principles to foster the competency of translating technological, pedagogical, and content knowledge into action in teacher education contexts.…”
Section: Design-based Learning Pedagogymentioning
confidence: 99%
“…Swan et al [26] explored a collaborative, design-based approach to improving the learning effects in core courses of an online program. Gómez Puente et al [27] boosted teachers to use the DBL theoretical framework to create teaching activities and proposed an immersive learning model to enhance teachers' professionalism. Baran and Uygun [28] outlined eight DBL principles to foster the competency of translating technological, pedagogical, and content knowledge into action in teacher education contexts.…”
Section: Design-based Learning Pedagogymentioning
confidence: 99%
“…Reflecting on the positive impact of prototyping on students' emotional experience, this would suggest DBL educators could orchestrate the session of prototyping as a moment for students to engage and enjoy. On the other hand, getting feedback from others, as a way of receiving summative assessment in DBL (Gómez Puente et al 2015), was found to be positively related to relaxation feelings, which can also facilitate learning evaluation. Future design considerations in terms of DBL classroom management may foster students' relaxation and reflection by facilitating feedback moments in groups.…”
Section: The Variable Impact Of Emotionsmentioning
confidence: 99%
“…Learning in educational ecosystems is often experiential in nature and hands-on and learning in higher education is expected to take this form more and more (Flynn & Vredevoogd, 2010). As such, inquiry-, problem-or cased-based learning or designbased learning are suitable educational methods (Gomez Punte, van Eijck, & Jochems 2015). In such approaches students will learn by creatively solving problems or cases, or by creating designs (Davies et al, 2013).…”
Section: Pedagogymentioning
confidence: 99%